2016
DOI: 10.1002/jbio.201600166
|View full text |Cite
|
Sign up to set email alerts
|

Removal of naturally grown human biofilm with an atmospheric pressure plasma jet: An in‐vitro study

Abstract: The removal of biofilm is a prerequisite for a successful treatment of biofilm‐associated diseases. In this study, we compared the feasibility of an atmospheric pressure plasma device with a sonic powered brush to remove naturally grown supragingival biofilm from extracted teeth. Twenty‐four periodontally hopeless teeth were extracted. Argon jet plasma with an oxygen admixture of 1 vol% and a sonically driven brush were used to remove biofilm with application times of 60 s, 180 s and 300 s. The treatment effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…The application of argon−oxygen plasma is able to remove the organic material of the dental enamel, while the minerals are left on the surface. An increase of PO 4 may take place, which confirms that the hydroxyapatite is left on the surface after plasma exposure (Jablonowski et al, ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The application of argon−oxygen plasma is able to remove the organic material of the dental enamel, while the minerals are left on the surface. An increase of PO 4 may take place, which confirms that the hydroxyapatite is left on the surface after plasma exposure (Jablonowski et al, ).…”
Section: Discussionmentioning
confidence: 68%
“…In chromium−cobalt alloys, differences in the OH − percentages were observed with the oxygen plasma application, which showed that the method is effective for cleaning and surface activation (Paredes et al, ). The argon plasma application with 1.0 vol% oxygen admixture also has the effect of enamel chemical cleaning, reducing the organic compounds and increasing mineral compound concentration (Jablonowski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to oral biofilm inactivation, the study in beagles observed a larger amount of new bone formation in the bone‐to‐implant contact surface area in the plasma group . In another study, the ability to remove naturally grown biofilms on teeth with plasma treatment was compared to sonic brush, and biofilm removal was comparable for both treatments …”
Section: Discussionmentioning
confidence: 99%
“…24 In addition to oral biofilm inactivation, the study in beagles observed a larger amount of new bone formation in the bone-to-implant contact surface area in the plasma group. 25 In another study, the ability to remove naturally grown biofilms on teeth with plasma treatment was compared to sonic brush, and biofilm removal was comparable for both treatments. 25 However, it is important to note that killing the biofilm is not enough for its removal, considering there are other biofilm products that play a role in peri-implantitis, including cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation